Effect of ice accretion on aerodynamic characteristics of pipeline suspension bridges. (December 2022) - Yu, Haiyan; Zhang, Mingjie; Xu, Fuyou
Abstract: Pipeline suspension bridges may confront the issue of ice accretion in areas prone to glaze ice or rime. Ice accretion is known to influence the wind-induced responses of various structures, while the effects on the wind-induced responses of pipeline suspension bridges received little attention. To this end, this paper investigated the effect of ice accretion on the aerodynamic characteristics of pipeline suspension bridges from a series of wind tunnel tests. The influences of the shape of cross-section, ice shape, ice class, and Reynolds number on mean aerodynamic force coefficients were examined through static wind tunnel tests. The galloping stability was further examined based on the quasi-steady galloping theory according to the mean aerodynamic force coefficients. Furthermore, the effects of ice class and ice shape on the aeroelastic stability and flutter derivatives of a pipeline suspension bridge were investigated through dynamic wind tunnel tests. The results comprehensively reveal how ice accretion affects the aerodynamic characteristics of the bridge. Ice accretion on the girder can increase the static aerodynamic force, probability of galloping, and leads to vortex-induced vibration. Research results can provide a basis for aerostatic and buffeting analyses and a reference for the wind-resistant design of similar bridges in cold regions.